2014
DOI: 10.1585/pfr.9.3405122
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Butt Joint Composed of Nb<sub>3</sub>Sn Cable-In-Conduit Conductors

Abstract: To evaluate butt joint fabrication technology of Nb 3 Sn cable-in-conduit (CIC) conductors, joint resistance and quench current were measured using a joint sample developed for the JT-60SA central solenoid (CS) coil. The measurements indicate that the butt joint fulfilled the design requirements. To simulate the butt joint characteristics, a one-dimensional numerical model simplifying the butt joint configuration was developed. Using the model, joint resistance and quench current of the butt joint were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…44 shows the measurement results of joint resistance. The measurements indicated that the performance of the pancake joint fulfilled the design requirement in which the joint resistance was less than 5 nΩ at 2 T [23].…”
Section: Measurements Of Joint Resistancementioning
confidence: 85%
See 1 more Smart Citation
“…44 shows the measurement results of joint resistance. The measurements indicated that the performance of the pancake joint fulfilled the design requirement in which the joint resistance was less than 5 nΩ at 2 T [23].…”
Section: Measurements Of Joint Resistancementioning
confidence: 85%
“…37 and 38. The sample is hairpin-shaped and consists of two butt joints using the JT-60SA CS coil conductors [23,24]. The sample has a single inlet and double outlets for SHe.…”
Section: Joint Samplementioning
confidence: 99%
“…All coils are wound with Nb 3 Sn CIC conductors. Each pancake coil is connected through butt joints [15][16][17] of the conductor. The number of coil winding layers is 52.…”
Section: Ms Pancake Coil and Nb 3 Sn Cic Conductormentioning
confidence: 99%
“…In Table 2, the specification of the CS conductor is listed. Each coil was connected through butt joints [8,9] of the conductors.…”
Section: Jt-60 Sa Cs1 Modulementioning
confidence: 99%
“…The conductor lengths of the model coil and the CS1 module were approximately 200 m and 2600 m, respectively. In the CS1 module, as described in Section 2, each pancake coil was connected using butt joint technology where two superconducting cables were connected through a 0.1 mm-thick-copper sheet by diffusion bonding [8,9]. Therefore, loop currents, which are supercurrents, cannot flow along the entire length of the CS1 module due to the resistance of the butt joint while holding coil current after coil excitation and degauss.…”
Section: -1 Comparison Between the Cs1 Module And The Cs Model Coil I...mentioning
confidence: 99%